Sie sind auf Seite 1von 36

Kuboktaeder

Kuboktaeder

Kuboktaeder, Bestimmung von V

s
s
s =

2 a
2

1 s2
8 s
3 2

= (2s)

= 8s3

20 3
20 2
=
s =
( a)
3
3 2

4 3
s
3
3

5 2 3
a
3
3

Aufbau des Kuboktaeders

1.

2.

3.

4.

5.

6.

7.

8.

9.

10.

11.

12.

13.

14.

Aufbau des Kuboktaeders


e
1.

4-Eck

2.

3-Eck

3.

3-Eck

4.

3-Eck

5.

3-Eck

6.

4-Eck

7.

4-Eck

8.

4-Eck

9.

4-Eck

10.

3-Eck

11.

3-Eck

12.

3-Eck

13.

3-Eck

14.

4-Eck

Bautyp

II

Aufbau des Kuboktaeders


e

1.

4-Eck

2.

3-Eck

3.

3-Eck

4.

3-Eck

10

5.

3-Eck

12

6.

4-Eck

14

7.

4-Eck

10

16

8.

4-Eck

11

18

9.

4-Eck

12

20

10.

3-Eck

12

21

10

11.

3-Eck

12

22

11

12.

3-Eck

12

23

12

13.

3-Eck

12

24

13

14.

4-Eck

12

24

14

Bautypen I, II :
I

k = e+f
2 = 1+1

II

k = e+f
1 = 0+1
k = e+f
k = (e+f)
k = e+f + c ,
4 = 4+1 + c
c = -1
k = e+f - 1
k = e+f - 1
e-k+f = 1

Bautyp III :
e-k+f = 2

c konstant

Bautyp

II

III

Aufbau des Kuboktaeders

1.

2.

3.

4.

5.

6.

7.

8.

9.

10.

11.

12.

13.

14.

Aufbau des Kuboktaeders


e
1.

4-Eck

2.

3-Eck

3.

3-Eck

4.

3-Eck

5.

3-Eck

6.

4-Eck

7.

4-Eck

8.

4-Eck

9.

4-Eck

10.

3-Eck

11.

3-Eck

12.

3-Eck

13.

3-Eck

14.

4-Eck

Bautyp

II

Aufbau des Kuboktaeders


e

1.

4-Eck

2.

3-Eck

3.

3-Eck

4.

3-Eck

10

5.

3-Eck

12

6.

4-Eck

14

7.

4-Eck

10

16

8.

4-Eck

11

18

9.

4-Eck

12

20

10.

3-Eck

12

21

10

11.

3-Eck

12

22

11

12.

3-Eck

12

23

12

13.

3-Eck

12

24

13

14.

4-Eck

12

24

14

Bautypen I, II :
I

k = e+f
2 = 1+1

II

k = e+f
1 = 0+1
k = e+f
k = (e+f)
k = e+f + c ,
4 = 4+1 + c
c = -1
k = e+f - 1
k = e+f - 1
e-k+f = 1

Bautyp III :
e-k+f = 2

c konstant

Bautyp

II

III